PERAN REGULASI TINGKAT KOMPONEN DALAM NEGERI (TKDN) DALAM KERJA SAMA PEMERINTAH DAN BADAN USAHA (KPBU) PADA SEKTOR INFRASTRUKTUR DI INDONESIA DAN NEGARA ASEAN: TANTANGAN DALAM INVESTASI ASING - Sofwah, Salsabila; Delion, Wilson; Wira, M Daffa Sahrim; Ravandito, Arenza; Velentina, Rouli Anita (Jurnal Yuridis, 2025)
This study examines the role of local content requirements regulations in Public-Private Partnership (PPP) schemes within Indonesia’s infrastructure sector, and compares it with Vietnam’s policy approach. Local content requirements regulations aim to strengthen domestic industries, create employment, and reduce reliance on imported products by prioritizing the use of local goods and services. However, their implementation also presents challenges, especially in attracting foreign investors who require flexibility in supply chains and technology access. The case study of the Cirata Floating Solar Power Plant project illustrates the technical and administrative application of local content requirements and how foreign investors adjust their business strategies accordingly. Compared to Vietnam, which adopts a more incentive-based approach through price preferences without explicit TKDN obligations—Indonesia enforces stricter requirements. The study emphasizes the need for a balanced policy that protects local industries while fostering a competitive investment climate to ensure sustainable infrastructure development. Keywords : local content requirements, PPP, foreign investment, infrastructure